Dissolved organic carbon fluxes by seagrass meadows and macroalgal beds - Barrón, Cristina; Apostolaki, Eugenia T.; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
Estimates of dissolved organic carbon (DOC) release by marine macrophyte communities (seagrass meadows and macroalgal beds) based on in situ benthic chambers from published and unpublished are compiled in this study. The effect of temperature and light availability on DOC release by macrophyte communities was examined. Almost 85 % of the seagrass communities and all of macroalgal communities examined acted as net sources of DOC. Net DOC fluxes in seagrass communities increase positively with water temperature. In macroalgal communities net DOC fluxes under light exceeded those under dark condition, however, this trend was weaker in seagrass communities. Shading of a mixed seagrass meadow in The Philippines led to a significant reduction on the net DOC release when shading was maintained for 6 days compared to only 2 days of shading. Net DOC fluxes increased with increasing community respiration, but were independent of primary production or net community production. The estimated global net DOC flux, and hence export, from marine macrophytes is about 0.158 ± 0.055 Pg C yr-1 or 0.175 ± 0.056 Pg C yr-1 depending on the global extent of seagrass meadows considered.